Pengaruh Leverage terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening di Masa Pandemi COVID-19 pada Sektor Transportasi di BEI - Muhammad Fathoni; Devi Rusvitawati (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2026)
This study investigates the effect of leverage on firm value with profitability as an intervening variable during the COVID-19 pandemic, focusing on transportation sector companies listed on the Indonesia Stock Exchange (IDX). The research adopts an associative quantitative approach using Smartpls software for path analysis. Leverage is measured by Debt to Equity Ratio (DER), firm value by Price to Book Value (PBV), and profitability by Return on Equity (ROE). A total of 10 transportation companies were selected through purposive sampling, covering the period from 2019 to 2023. The results reveal that leverage has a positive and significant effect on both firm value and profitability. However, profitability does not significantly affect firm value and fails to mediate the relationship between leverage and firm value. These findings suggest that during crisis periods, particularly under government-imposed social restrictions (PSBB), investors prioritize financial structure over short-term earnings. This implies a strategic shift in managerial and investor focus from profitability to capital resilience. The study recommends that transportation firms adopt adaptive leverage strategies, and that policymakers provide fiscal support—such as credit relaxation and tax incentives—to help the sector manage financial risks and sustain firm value in times of economic uncertainty.